Musculoskeletal pain is associated with very low levels of vitamin D in men: results from the European Male Ageing Study. Issue 8 (24th May 2010) - McBeth, John; Pye, Stephen R; O'Neill, Terence W; Macfarlane, Gary J; Tajar, Abdelouahid; Bartfai, Gyorgy; Boonen, Steven; Bouillon, Roger; Casanueva, Felipe; Finn, Joseph D; Forti, Gianni; Giwercman, Aleksander; et al.
Abstract : Introduction: A study was undertaken to test the hypothesis that musculoskeletal pain is associated with low vitamin D levels but the relationship is explained by physical inactivity and/or other putative confounding factors. Methods: Men aged 40–79 years completed a postal questionnaire including a pain assessment and attended a clinical assessment (lifestyle questionnaire, physical performance tests, 25-hydroxyvitamin D3 (25-(OH)D) levels from fasting blood sample). Subjects were classified according to 25-(OH)D levels as 'normal' (≥15 ng/ml) or 'low' (<15 ng/ml). The relationship between pain status and 25-(OH)D levels was assessed using logistic regression. Results are expressed as ORs and 95% CIs. Results: 3075 men of mean (SD) age 60 (11) years were included in the analysis. 1262 (41.0%) subjects were pain-free, 1550 (50.4%) reported 'other pain' that did not satisfy criteria for chronic widespread pain (CWP) and 263 (8.6%) reported CWP. Compared with patients who were pain-free, those with 'other pain' and CWP had lower 25-(OH)D levels (n=239 (18.9%), n=361 (23.3) and n=67 (24.1%), respectively, p<0.05). After adjusting for age, having 'other pain' was associated with a 30% increase in the odds of having low 25-(OH)D while CWP was associated with a 50% increase. These relationships persisted after adjusting for physical activity levels. Adjusting for additional lifestyle factors (body mass index, smoking and alcohol use) and depression attenuated these relationships, although pain remained moderately associated with increased odds of 20% of having low vitamin D levels. Conclusions: These findings have implications at a population level for the long-term health of individuals with musculoskeletal pain.